Prostaglandin E2-EP2/EP4 signaling induces immunosuppression in human cancer by impairing bioenergetics and ribosome biogenesis in immune cells - Punyawatthananukool, Siwakorn; Matsuura, Ryuma; Wongchang, Thamrong; Katsurada, Nao; Tsuruyama, Tatsuaki; Tajima, Masaki; Enomoto, Yutaka; Kitamura, Toshio; Kawashima, Masahiro; Toi, Masakazu; Yamanoi, Koji; Hamanishi, Junzo; et al. (Nature communications, 2024)
While prostaglandin E 2 (PGE 2 ) is produced in human tumor microenvironment (TME), its role therein remains poorly understood. Here, we examine this issue by comparative single-cell RNA sequencing of immune cells infiltrating human cancers and syngeneic tumors in female mice. PGE receptors EP4 and EP2 are expressed in lymphocytes and myeloid cells, and their expression is associated with the downregulation of oxidative phosphorylation (OXPHOS) and MYC targets, glycolysis and ribosomal proteins (RPs). Mechanistically, CD8 + T cells express EP4 and EP2 upon TCR activation, and PGE 2 blocks IL-2-STAT5 signaling by downregulating Il2ra , which downregulates c-Myc and PGC-1 to decrease OXPHOS, glycolysis, and RPs, impairing migration, expansion, survival, and antitumor activity. Similarly, EP4 and EP2 are induced upon macrophage activation, and PGE 2 downregulates c-Myc and OXPHOS in M1-like macrophages. These results suggest that PGE 2 -EP4/EP2 signaling impairs both adaptive and innate immunity in TME by hampering bioenergetics and ribosome biogenesis of tumor-infiltrating immune cells. Mechanisms of prostaglandin E2 (PGE2)-mediated immunosuppression in the tumor microenvironment (TME) have been previously reported. Here, the authors profile PGE2 functions in human cancer, suggesting that prostaglandin E2-mediated signaling impairs the activity of human CD8+ T cells and macrophages by altering bioenergetics and ribosome biogenesis.